Ultrasound influence on exciton emission of GaP light diodes - Gontaruk, O.M.; Khivrych, V.I.; Pinkovska, M.B.; Tartachnyk, V.P.; Olikh, Ya.M.; Vernydub, R.M.; Opilat, V.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Electroluminescence of GaP light diodes, treated by ultrasound at room and low temperatures has been studied. It has been found that short ultrasound caused improvement of red diode emission characteristics while electroluminescence degradation occurred in structures treated by prolong treatment at room temperature. Spectral curves measured under acoustic dynamic mode possess some specific features concerning fine structure. If reverse biased diodes possess microplasma initially, ultrasound action decreases its brightness. Possible mechanisms of the ultrasonic interaction with crystal structure defects have been discussed.